2022
DOI: 10.1111/jnc.15685
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate receptor modulators in stroke treatment

Abstract: Globally, stroke is a primary reason for death and lasting disability (Benjamin et al., 2019). Inflammation is critical in the course of a stroke and is closely linked to prognosis (Anrather & Iadecola, 2016).The inflammatory response following stroke involves immune cell infiltration, glial cell activation, and the emission of diverse neurotoxic molecules, such as pro-inflammatory cytokines, matrix metalloproteinases, and nitric oxide synthase, which further exacerbates neurological damage by causing endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…At the level of the central nervous system (CNS), modulators (antagonists) of S1PR1 signaling, like fingolimod, have specific actions on every CNS cell type: (i) in endothelial cells, by reducing the permeability of the blood–brain barrier (BBB), decreasing expression of ICAM-1, and reducing the binding of leukocytes to endothelial cells; (ii) in neurons, by preventing apoptosis and protecting from excitotoxic death; (iii) in astrocytes, by inhibiting the production of proinflammatory cytokines, chemokines, and neurotoxic substances (e.g., IL-6, COX2, VEGF), by increasing the production of neuroprotective factors and by preventing the activation and proliferation of astrocytes; (iv) in microglia, by reducing microglia activation, reducing the production of proinflammatory cytokines (IL-6), and by promoting polarization to M2 phenotype; (v) in oligodendrocytes, by promoting the renewal of oligodendrocytes and enhancing remyelination. In conclusion, fingolimod reduces inflammation, excitotoxicity, glial activation and polarization, and BBB destruction, and improves neurogenesis [ 42 ]. For all these reasons, fingolimod has a beneficial effect on different neurological disorders such as stroke [ 42 ], hypoxia [ 43 ], and epilepsy [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the level of the central nervous system (CNS), modulators (antagonists) of S1PR1 signaling, like fingolimod, have specific actions on every CNS cell type: (i) in endothelial cells, by reducing the permeability of the blood–brain barrier (BBB), decreasing expression of ICAM-1, and reducing the binding of leukocytes to endothelial cells; (ii) in neurons, by preventing apoptosis and protecting from excitotoxic death; (iii) in astrocytes, by inhibiting the production of proinflammatory cytokines, chemokines, and neurotoxic substances (e.g., IL-6, COX2, VEGF), by increasing the production of neuroprotective factors and by preventing the activation and proliferation of astrocytes; (iv) in microglia, by reducing microglia activation, reducing the production of proinflammatory cytokines (IL-6), and by promoting polarization to M2 phenotype; (v) in oligodendrocytes, by promoting the renewal of oligodendrocytes and enhancing remyelination. In conclusion, fingolimod reduces inflammation, excitotoxicity, glial activation and polarization, and BBB destruction, and improves neurogenesis [ 42 ]. For all these reasons, fingolimod has a beneficial effect on different neurological disorders such as stroke [ 42 ], hypoxia [ 43 ], and epilepsy [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, fingolimod reduces inflammation, excitotoxicity, glial activation and polarization, and BBB destruction, and improves neurogenesis [ 42 ]. For all these reasons, fingolimod has a beneficial effect on different neurological disorders such as stroke [ 42 ], hypoxia [ 43 ], and epilepsy [ 44 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the level of the central nervous system (CNS), modulators (antagonists) of S1PR1 signaling, like ngolimod, have speci c actions on every CNS cell type: i) in endothelial cells, by reducing the permeability of the blood-brain barrier (BBB), decreasing expression of ICAM-1, and reducing the binding of leukocytes to endothelial cells; ii) in neurons, by preventing apoptosis and protecting from excitotoxic death; iii) in astrocytes, by inhibiting the production of proin ammatory cytokines, chemokines and neurotoxic substances (e.g., IL-6, COX2, VEGF), by increasing the production of neuroprotective factors and by preventing the activation and proliferation of astrocytes; iv) in microglia, by reducing microglia activation, reducing the production of proin ammatory cytokines (IL-6), and by promoting polarization to M2 phenotype; v) in oligodendrocytes, by promoting the renewal of oligodendrocytes and enhancing remyelination. In conclusion, ngolimod reduces in ammation, excitotoxicity, glial activation and polarization, and BBB destruction, and improves neurogenesis [42]. For all these reasons, ngolimod has a bene cial effect on different neurological disorders such as stroke [42], hypoxia [43], and epilepsy [44], [45], [46], [47].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, ngolimod reduces in ammation, excitotoxicity, glial activation and polarization, and BBB destruction, and improves neurogenesis [42]. For all these reasons, ngolimod has a bene cial effect on different neurological disorders such as stroke [42], hypoxia [43], and epilepsy [44], [45], [46], [47].…”
Section: Discussionmentioning
confidence: 99%
“…Through subsequent hydrogenation, reduction, and substitution steps, benzyl bromide 8 was obtained as the key intermediate for further transformations. Although the total yield was not explicitly mentioned in the Novartis’ patents, previous studies in 2017 reported a yield of 63.7% over four steps using similar approaches . Despite the concise nature of the coupling methodologies, the expensive starting materials (>$1300/kg according to Scifinder n ) and the requirement for noble-metal catalysts posed challenges in terms of budget control during process development.…”
Section: Introductionmentioning
confidence: 99%